Interactions between Innate Immunity, Microbiota, and Probiotics - GianMarco Giorgetti; Giovanni Brandimarte; Federica Fabiocchi; Salvatore Ricci; Paolo Flamini; Giancarlo Sandri; Maria Cristina Trotta; Walter Elisei; Antonio Penna; Piera Giuseppina Lecca; Marcello Picchio; Antonio Tursi (Journal of Immunology Research)
The term “microbiota” means genetic inheritance associated with microbiota, which is about 100 times larger than the guest. The tolerance of the resident bacterial flora is an important key element of immune cell function. A key role in the interaction between the host and the microbiota is played by Paneth cell, which is able to synthesize and secrete proteins and antimicrobial peptides, such as α/β defensins, cathelicidin, 14 β-glycosidases, C-type lectins, and ribonuclease, in response to various stimuli. Recent studies found probiotics able to preserve intestinal homeostasis by downmodulating the immune response and inducing the development of T regulatory cells. Specific probiotic strain, as well as probiotic-driven metabolic products called “postbiotics,” has been recently recognized and it is able to influence innate immunity. New therapeutic approaches based on probiotics are now available, and further treatments based on postbiotics will come in the future.